2012
DOI: 10.1111/j.1574-6968.2012.02632.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of 5S rRNA genes within individual prokaryotic genomes

Abstract: We examined intragenomic variation of paralogous 5S rRNA genes to evaluate the concept of ribosomal constraints. In a dataset containing 1161 genomes from 779 unique species, 96 species exhibited > 3% diversity. Twenty‐seven species with > 10% diversity contained a total of 421 mismatches between all pairs of the most dissimilar copies of 5S rRNA genes. The large majority (401 of 421) of the diversified positions were conserved at the secondary structure level. The high diversity was associated with partial rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…variecolor NRRL 1858 displays branched unpaired region where as isolate CLB38 appeared linear in structure and also variations in stem/loop transition were observed ( Fig 5 ). ITS2 RNA structures are sensible to single base changes which in turn can affect hydrogen base pairing in stem and loop secondary structures [ 50 ].A non-conserved mismatches might altered base-pairing and stem to loop transitions by counterparts [ 42 , 51 ]. Studies have reported many fungi might express different life-styles in response to environmental factors or host genotype [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…variecolor NRRL 1858 displays branched unpaired region where as isolate CLB38 appeared linear in structure and also variations in stem/loop transition were observed ( Fig 5 ). ITS2 RNA structures are sensible to single base changes which in turn can affect hydrogen base pairing in stem and loop secondary structures [ 50 ].A non-conserved mismatches might altered base-pairing and stem to loop transitions by counterparts [ 42 , 51 ]. Studies have reported many fungi might express different life-styles in response to environmental factors or host genotype [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, a series of emerimidine (A-B) derived from endophytic fungus Emericella sp. HK-ZJ which isolated from the inner bark of the mangrove plant Aegiceras corniculatum (Myrsinaceae) has been reported to show anti-influenza A viral (H 1 N 1 ) activity [ 51 ]. Thus, from the present study, it suggests that the antimicrobial potential of these isolated metabolites might play a significant role in symbiotic benefits of endosymbiont to the host.…”
Section: Resultsmentioning
confidence: 99%
“…Species of bacteria often contain multiple copies of the ribosomal operon, and each has its own distinct phylogenetic diversity; intragenomic variability in the 16S gene has been studied most commonly (Větrovský and Baldrian 2013;Coenye and Vandamme 2003) , but there are also studies on the 23S and 5S genes (Pei et al 2012(Pei et al , 2009) . When we consider the evolutionary history of all copies of the ribosomal RNA operons from a given species, one underlying assumption is that all those copies should be monophyletic, i.e.…”
mentioning
confidence: 99%
“…Species of bacteria often contain multiple copies of the ribosomal operon, and each has its own distinct phylogenetic diversity; intragenomic variability in the 16S gene has been studied most commonly ( 20 , 21 ), but there are also studies on the 23S and 5S genes ( 22 , 23 ). When we consider the evolutionary history of all copies of the ribosomal RNA operons from a given species, one underlying assumption is that all those copies should be monophyletic, i.e.…”
Section: Resultsmentioning
confidence: 99%